Freeing us from pandemic alienation: Tea-based online expressive arts therapy. (1st December 2021) - Kwong (Aleck), Man-Kit
This article creatively presents a framework of conducting expressive arts therapy online during the COVID-19 pandemic. The aim is to help people tap into the four modes of being through multimodal arts to respond to the alienation in each of them due to the pandemic. Tea, which has similarities with watercolour but is more natural and easily accessible, serves as the core art material in the creative process. This article includes experience of the participants who voluntarily joined a one-off online workshop, giving a clearer picture of the therapeutic process and changes. The relevance of tea to the four modes of being is discussed, and the ways in which the framework can be implemented are explored.